Duchowni, instytucje i organizacje kościelne w życiu literackim międzywojennego Poznania - Biesiada, Jacek (Ecclesia. Studia z Dziejów Wielkopolski, 2018)
Among the people who created the ambiance of the Poznań literary life in the interwar period were priests-men of letters, such as the poet Ewaryst Nawrowski, the authors of reportages and memoirs - Nikodem Cieszyński, Ignacy Posadzy, Józef Kłos. An important part was played by priests-men of learning linked to the University of Poznań and the Poznań Seminary who presented their works at sessions of the Poznań Society of Friends of Sciences but also gave talks to more general audiences during events held both by Church and lay organizations. This group included among other such priests as Bronisław Gładysz, Kazimierz Kowalski, Władysław Hozakowski, Edward Warmiński. The Church culture forming center was the St. Adalbert Booksellers, an important publisher of Polish and world literature, which also published a cultural journal for the intelligentsia called “Tęcza”. Another such center was the Principal Institute of Catholic Action, publisher of the “Kultura” weekly, one of the leading journals of this profile in Poland.